Leadership for the Future: Enhancing Principal Preparation Through Standards and Innovation - Bonnie C. Fusarelli; Lance D. Fusarelli (Education Sciences)
This manuscript presents a comprehensive analysis of NC State University’s redesigned principal preparation program, emphasizing its alignment with state and national leadership standards, innovative curriculum, and commitment to practical application. The program’s redesign addresses long-standing criticisms of traditional university-based leadership preparation, such as the disconnect between theory and practice, by incorporating data-driven instructional leadership, equity-focused training, and collaborative community engagement. Additionally, this article explores the role of specialized internships, full-time residencies, and the integration of technology in training future principals. The program’s success is demonstrated by improved principal placement, school outcomes, and teacher retention—particularly in high-need schools. Finally, the manuscript discusses the future of leadership preparation, highlighting the potential of artificial intelligence to further enhance decision-making, personalized professional development, and administrative efficiency, while addressing ethical considerations such as data privacy and equity.